(untitled) (Bangladesh Journal of Child Health, 2024)
Background: Masturbation is not uncommon in younger children. Due to variable presentation in early childhood often leads to misdiagnosis and may result in unnecessary investigation and treatment. Materials & Method: This retrospective case study was conducted at outpatient department of Rehabilitation and Neurology unit of Dr.M R Khan Shishu Hospital and Institute of Child Health between 2013-2019. Result: Among 40 patients, majority (90%) had age of onset within 36 months of age. Mean and median age were 27.45 months and 25.5 months respectively, the range was between 4 months to 84 months. Male: female was 1:1.2. Most of the children came from urban area (85%) and from single family (77.5%). All 40 children shared common features like stereotype movement with variable duration, no alteration of consciousness, cessation with distraction when attempted, remained responsive during the events, their neurological examination was normal and no abnormalities were detected in laboratory studies. Thirty- three (82.5%) children did this behaviour on prone position. Thirty-one (77.5%) children had vocalization. Duration of episode was 5-10 min in 19(47.5%) children. Frequency of masturbation was up to 5 times per day in 30(75%) children. Twenty-two (55%) children did this behaviour when remained unnoticed. Antiepileptic drug was given to 14(35%) children but had no clinical improvement. Home video recordings were available in 18(43.9%) children. Conclusion: Early diagnosis from the knowledge of clinical manifestations helps to minimize unnecessary laboratory investigations and use of drugs. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 71-75